Research on electromagnetic radiation interference of high voltage pulse device. Issue 1 (March 2020) - Xu, Yuheng; Zhang, Xiangjin; Wang, Ruibo; Yue, Lianyong
Abstract: In view of the strong electrostatic field interference caused by the miniaturization of high voltage pulse capacitor circuit, the protection method of electronic equipment under the strong electrostatic field interference of high voltage pulse device is proposed. Based on the background of miniaturization of all electronic security system, a high-voltage capacitor pulse discharge model is established. The surrounding radiation of high-voltage capacitor instantaneous discharge is simulated by using the COMSOL software. The electromagnetic radiation interference of high-voltage capacitor to the system is analyzed, and the anti-radiation interference measures are proposed based on the electromagnetic shielding mechanism. It provides a basis for the actual circuit design and structure layout, and provides a reference for the stability and safety of the electronic security system and further miniaturization development.